Glaciation change in the northern part of the Middle Range on the Kamchatka Peninsula in the second half of the XX century - A. Ya. Muraviev; G. A. Nosenko (Лëд и снег, 2015)
The paper examines changes in surface area of glaciers in the north of Middle Ridge (Kamchatka Peninsula) occurred in the 1950s to the present. For this purpose, we used ASTER satellite imageries (2002), data of the USSR Glacier Inventory and aerial photographs of 1950. Vector boundaries of glacier maps were created by the decoding of ASTER images. The received estimates show glaciers decline in this area of Kamchatka. The glacier area of Middle Ridge, presented in the USSR Glacier Inventory, diminished by 16.6%. Reduced glacier area is subject to change major climatic factors. During this period the average summer air temperatures is increasing and the amount of solid precipitation reduced.